The application of maṣlaḥah in deciding faskh and ḥaḍānah cases in sharīᶜah court of federal territory of Kuala Lumpur - Naping, Herna; Mahmud, Mek Wok (IIUM Press, International Islamic University Malaysia, 2017)
This research seeks to analyse the application of ma ṣ la ḥ ah in settling the cases of faskh and ḥ a ḍ ānah in the Sharī ᶜ ah Court of the Federal Territory of Kuala Lumpur. Another primary focus of this research is to address the importance of the applicability of maqāsid al-sharī ᶜ ah and ma ṣ la ḥ ah in family conflicts without rigidly applying a certain view of an Islamic school of thought. A total of 20 decided court cases were collected and analysed, ten faskh and another ten ḥ a ḍ ānah cases, which constitute as supporting data. Two methodological instruments were adopted to collect data; the first instrument was library research where various sources including books, documents, court cases and statutes were reviewed. The second instrument was analysis of court cases retrieved from the Sharī ᶜ ah Court of Federal Territory of Kuala Lumpur. The findings indicate that the Court acknowledges the various sources of law which were not mainly and solely articulated based on the view of the Shāfi ᶜ ī school of thought. The judge in some occasions had duly applied the concept of ma ṣ la ḥ ah in the sense that he was exercising his ijtihād if he found that there was a lacuna in the statutory law. He was capable of coming up with a departing reference from the provision in order to reach a just decision. These results demonstrate the success of the proposed examination in achieving the objectives of this study.